KUMPULAN PUISI SURAT UNTUK IBU KARYA RATIHSANGGARWATI : ANALISIS SEMIOTIK RIFFATERRE - , HETA PANCA LAKSMI S, Drs. Heru Marwata, M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research is taken from Surat Untuk Ibu Ratihâs poem collection where as the main character is mother. This poem is analysed using semiotic Riffaterre theory. The first step is looking up the indirect expression and the semiotic reading itself. The indirect expression consists of the meaning changing (metafora and metonimy), deviation (ambiguity, contradicty, and unmeaningless), meaning created (poetry, enjambement, homologue, and typhography). Exept that the indirect expression is used to find out the meaning that is needed in heuristic and hermeneutic reading and matrix, type, variant, and hipogram reading. Kualitative method is used in this research that is interpretation advantages in the from of descriptive. The step have to be done in this research is to ascertain the study object, population, sample, and study object analyze itself. The result of this research is metonymy and poetry in the indirect espression. It is also the meaning discovery from the semiotic reading that is the heuristic and hermeneutic, matrix, type, variant, and hipogram reading.